Komparasi Hukum Tentang Ketentuan Perkawinan Poligami Di Indonesia dan Mesir - Rani Nur Azizah (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This article seeks to conduct a comparative analysis of the legal frameworks governing polygamous marriage in Indonesia and Egypt. There are fundamental differences between the two countries regarding the regulation of polygamy. This study adopts a library research method with a descriptive-comparative approarch, utilizing documentation as the primary data collection technique and comparative analysis for data interpretation. The findings reveal that Indonesia prossesses a more comprehensive and detailed codifivation of laws concerning polygamous marriage compared to Egypt. In Indonesia, polygamy is regulated under several legal instruments, notably Law Number 1 of 1974 and Government Regulation Number 9 of 1975. In contrast in legal regulations between the two countries can be attributed, in part, to the different schools of Islamic jurisprudence each country follows; Indonesia predominantly adheres to the Syafi’i, whereas Egypt is more closely aligned with conservative interpretation. Nevertheless, both countries permit polygamous marriage. The primary distinction lies in the specific conditions and requirements imposed, with Indonesia enacting more detailed and stringent regulations compared to Egypt.